Ensino de leitura de palavras de sílaba inicial comum e a generalização recombinativa em pessoas com deficiência intelectual. - Zanin, Ana Beatriz (Universidade Federal de São Carlos, 2026)
The present study evaluated the effects of a teaching procedure based on the formation of equivalent stimulus classes, using words with a common initial syllable, on the acquisition of reading comprehension and recombinative reading in students with intellectual disabilities. Six students with intellectual disabilities, enrolled in the 3rd to 5th grades of elementary education in public and/or private schools, participated in the study. The general procedure included initial assessments, teaching conditional relations, tests for emergent relations, and probes of generalized reading. Instruction focused on the relations between dictated words and pictures (AB) and between dictated words and printed words (AC) across three stimulus sets. Emergence tests (BC and CB) were conducted to verify the formation of equivalent stimulus classes. Reading tests involving novel words generated through syllabic transposition and recombination of letters/syllables were administered before and after instruction. The results demonstrated that five participants learned directly taught relations (AB and AC), although individual differences were observed in the number of teaching exposures required. Five participants also demonstrated the emergence of BC and CB relations. In the reading of taught words (CDens), one participant correctly read all words during the pre-test, two participants correctly read between two and four words, and two participants did not correctly read any words. In the post-test, one participant maintained high performance in word reading, whereas the remaining four participants correctly read two or three novel words. Regarding recombinative generalization (CDgen), one participant demonstrated accurate reading of both recombined and syllabic transposition words, while two participants correctly read between 16% and 33% of the syllabic transposition words. The remaining three participants maintained low or null performance. These findings suggest that the procedure contributed to the formation of equivalence classes. However, further research is needed to investigate the variables associated with the emergence of oral reading and recombinative reading in individuals with intellectual disabilities.
Teaching reading of words with common initial syllables and recombinative generalization in people with intellectual disabilities
Keywords: Educação especial; Generalização Recombinativa; Equivalência de estímulos; Deficiência intelectual; Ensino de leitura; Sílaba inicial comum; Special education; Stimulus equivalence; Recombinative generalization; Intellectual disability; Reading instruction; Common prefix; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade